Activation of α7-nAChRs Promotes the Clearance of α-Synuclein and Protects Against Apoptotic Cell Death Induced by Exogenous α-Synuclein Fibrils - Zhao, Jifeng; Li, Yun; Li, Yan; Xu, Shi; Tao, Tingting; Hua, Ye; Zhang, Ji; Fan, Yi (Frontiers in Cell and Developmental Biology, 2021)
Misfolding and abnormal aggregation of α-synuclein (αSyn) are one of the leading causes for Parkinson's disease (PD). Finding some way to reduce the aggregation of αSyn is particularly important for the treatment of PD. The main route in prion-like αSyn spreading is the cholinergic innervated vagus nervous system and central cholinergic neurons. Since the degenerative changes and death of cholinergic neurons also run through the pathological process of PD, we hypothesize an involvement of the cholinergic system in αSyn aggregation. The α7 nicotinic acetylcholine receptors (α7-nAChRs) are one of the most abundant nAChRs in the mammalian brain. Using nicotine and a selective α7-nAChRs agonist PNU-282987, we found a protective effect of α7-nAChRs on the cell damage induced by αSyn-PFF (preformed fibrils) through inhibiting apoptotic cell death. We further discovered an additive effect of α7-nAChRs on the clearance of αSyn in normal and αSyn stably transduced SH-SY5Y cells. Moreover, using α7-nAChRs knockout mice, we noticed that α7-nAChRs deficiency increased the deposition of αSyn and aggravated the loss of dopaminergic neurons in a chronic MPTP mouse model of PD. Our findings for the first time indicated that α7-nAChRs activation exhibited a neuroprotective effect on αSyn pathology and aggregation by promoting the clearance of αSyn.